Expediente e Nominata - REVER, Redação (REVER: Revista de Estudos da Religião, 2020)
Avaliadores desta edição: Alex Villas Boas (UCP); Alexandre Palma (UCP); Alexandre Simão de Freitas (UFPE); Aloisio Cristovam dos Santos Junior (autônomo); Ana Carolina Mariani (autônoma); André de Campos Silva (ULisboa); António Camões Gouveia (UNL); Antonio Cleber Rudy (UDESC); Antonio Genivaldo C. de Oliveira (PUC-SP); Carlos André Silva de Moura (UPE); Cecilia Loreto Mariz (UERJ); Claudia Regina Kluck (autônoma); Cristina M. Rocha (Western Sydney University); Diana Espirito Santo (UC-CL); Donizete Rodrigues (UNL); Ediana Ferreira Mendes (UFOB); Eduardo Gross (UFJF); Elaine Costa Honorato (PUC-SP); Eliane Moura Silva (UNICAMP); Elisangela dos Anjos Paula Vieira (UNIDERP); Elizabeth Parente Costa (ISCT-IUL); Emerson José Sena da Silveira (UFJF); Fabio Carvalho Leite (PUC-Rio); Fátima Regina Gomes Tavares (UFBA); Francirosy Campos Barbosa (USP); Helena Corazza (ITESP); Inês Espada Vieira (UCP); João Manuel Duque (UCP); João Marques Eleutério (UCP); Joaquim A. B. Carneiro Monteiro (autônomo); Jorge Fonseca (UNL); José Brissos-Lino (ULusófona); José Luiz de Moraes Franco (IFPA); Josias Jacintho Bittencourt (UC); Karina Kosicki Bellotti (UFPR); Katia Simone Martins Mortari (UEL); Lélio Maximino Lellis (UNESP); Luís Lóia (UCP); Marcelo Simão Mercante (autônomo); Laura Viveiros de Castro Cavalcanti (UFRJ); Maximillian Ferreira Clarindo (autônomo); Mostafa Zekri (UNL); Oscar Javier Vergara Escobar (Juan N. Corpas); Pamela Siegel (UNICAMP); Patrícia Marcondes de Barros (UEL); Paulo Julião da Silva (UFPE); Paulo Mendes Pinto (ULusófona); Ramon Pereira dos Reis (autônomo); Raquel Aparecida de Oliveira (PUC-SP); Richard Gonçalves André (UEL); Rita Mendonça Leite (UCP); Roberto Serafim Simões (autônomo); Rodrigo Fadul Andrade (PUC-PR); Rodrigo Oliveira dos Santos (ACREPA); Rodrigo Portellan (UFJF); Rogério Gonçalves de Carvalho (IEC); Silas Guerriero (PUC-SP); Sylvio Fausto Gil Filho (UFPR); Taissa Tavernard de Luca (UEPA); Tiago Gurgel do Vale (PUC-SP)